A Case Study on Role of Kanchnaar Guggulu and Chandraprabhavati in the Management of Vatashtheela (BPH) - Garg, Ish; Yadav, Sujata (International Research Journal of Ayurveda & Yoga, 2022)
Benign Prostatic Hyperplasia (BPH) is a burning senile problem of elderly men, associated with lower urinary tract symptoms (LUTS). The prevalence figures vary from about 10-30% for men between 50-60 years of age to 25-45% in the age group of 70-80 years. BPH is a progressive disease that is presented as common symptoms such as frequent urination, urgency, nocturia, decreased and intermittent force of stream, and the sensation of incomplete bladder emptying. In Ayurveda, Vatashtheela disease closely resembles with Benign Prostatic Hyperplasia of modern medicine in its signs and symptoms. It is manifested due to improper function of Apana Vaat along with the vitiation of Kapha and Pitta Doshas. In this case study, the patient was administered Chandraprabha Vati & Kanchnaar Guggulu, at a dose of 1tab twice a day and 2tab twice a day respectively for two months. The irritative and obstructive symptoms of BPH (Vatashtheela) like frequency, urgency, staining, weak stream, incomplete emptying, nocturia, residual urine and size & weight of prostate were observed over the treatment. Analysis of result showed improvement in Vatashtheela (BPH). Finally study concluded that given treatment is found effective in management of Vatashtheela (BPH).